Mental Health and Welfare in Australian Anaesthetists. Issue 5 (September 2013) - Mcdonnell, N. J.; Kaye, R. M.; Hood, S.; Shrivaslava, P.; Khursandi, D. C. S.
This survey was designed to evaluate the factors affecting mental health and welfare in Australian anaesthetists and to investigate current sources of support. An electronic survey was sent to 500 randomly selected Fellows and trainees of the Australian and New Zealand College of Anaesthetists. Questions were related to: anxiety, stress, depression, substance misuse, self-medication, suicide, reporting illness, and help-seeking. Current psychological wellbeing was assessed using the Kessler Psychological Distress Scale (K10). A total of 191 completed surveys were received (a response rate of 38%): 26% had attended their general practitioner for mental health issues, of whom half had been diagnosed with a mental illness; 7% of all respondents were currently prescribed medication for this; 25% had previously self-prescribed psychoactive medication; 17% admitted to using alcohol to deal with stress, anxiety or depression; and 8% responded that mental illness had at some point impaired clinical care. Sixteen percent of all respondents reported previous suicidal ideation. Despite a low response rate, and the possibility of responder bias, the mental health of Australian anaesthetists would appear to be subject to common and persistent risk factors, many of which are well described in previous studies. We identify general practitioners as particularly valuable in targeting initiatives for improvements in mental health and welfare. The significant prevalence of suicidal ideation and reluctance to approach senior colleagues with concerns about mental health or welfare issues are specific causes for concern and suggest that further investigation, education and a potential review of support networks is required.